Cyber warfare impact to national security - Malaysia experiences - Azian, Ibrahim; Noorfadhleen, Mahmud; Nadrawina, Isnin; Dina Hazelbella, Dillah; Dayang Nurfauziah, Fauz Dillah (KnE Social Sciences, 2019)
This study analyzed the cyber warfare impact on national security and focusing on Malaysia experiences. The issues regarding cyber warfare have become a serious concern since it was a risk of national security in Malaysia. The objectives of the study are to analyze issues related to cyber warfare that affected Malaysian system security, to determine causes that caused to cyber warfare. This study used a qualitative research approach to evaluate the current defense approaches related to cyber warfare in Malaysia. The interviews were conducted with the respective respondents: the Senior Manager, Research Management Centre, Strategic Research, and Advisory Department of Cyber Security Malaysia Department. This study can contribute to expanding the security of national security by demanding the government to adopt a broad acquisition risk management strategy. It can assist in the development of highly effective aggressive and defensive methods to any company dealing with future cyber warfare challenges and risk.